2011
DOI: 10.1002/ase.251
|View full text |Cite
|
Sign up to set email alerts
|

Medical students' attitudes toward the anatomy dissection room in relation to personality

Abstract: Assessment of the personalities of medical students could enable medical educators to formulate strategies for the best development of academic and clinical competencies. In this article, we focus on the experience of students in the anatomy dissecting room. While there have been many attempts to evaluate the emotional responses of medical students to human cadaveric dissection, there has been no investigation into how different personality traits affect the responses. The main hypothesis tested was that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 14 publications
(11 reference statements)
8
50
1
7
Order By: Relevance
“…Consistent with earlier results on personality traits in medical students [48,49], we found low scores for neuroticism and high scores for agreeableness. Jerant et al [48] described the medical students in their sample as having higher levels of conscientiousness and agreeableness, similar levels of openness to experience and extraversion and lower levels of neuroticism, when compared to a general population sample.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with earlier results on personality traits in medical students [48,49], we found low scores for neuroticism and high scores for agreeableness. Jerant et al [48] described the medical students in their sample as having higher levels of conscientiousness and agreeableness, similar levels of openness to experience and extraversion and lower levels of neuroticism, when compared to a general population sample.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, very few studies have not found significant gender differences (Snelling et al, ; Leboulanger, ). Basal anxiety levels (measured as “trait anxiety”) are similar independently of gender and are perceived more acutely by female students (Abu‐Hijelh et al, ; Arráez‐Aybar et al, ; Plaisant et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, dissection is still the subject of debate and controversy (Ellis, ; McLachlan et al, ; Winkelmann, ; Böckers et al, ; Wilson et al, ). Around 16% of medical students claimed to have thoughts about diseases and death when faced with a cadaver (McLachlan et al, ; Lempp, ; Böckers et al, ; Plaisant et al, ; Goodwin et al, ). Anxiety is an emotional adaptive response to uncertain or alarming situations, and it forces us to take action and to find an appropriate response to deal with them.…”
Section: Introductionmentioning
confidence: 99%
“…If personality influences students' attitudes, the assessment of personality traits could also enable medical educators to formulate strategies for the best development of academic and clinical competence. 19 The main aim of this study was to determine whether personality traits are related to medical students' attitudes towards learning communication skills. Based on prior work in the field of medicine about personality and other attitudes [19][20][21] , we hypothesized that there would be a significant relationship.…”
Section: Introductionmentioning
confidence: 99%
“…19 The main aim of this study was to determine whether personality traits are related to medical students' attitudes towards learning communication skills. Based on prior work in the field of medicine about personality and other attitudes [19][20][21] , we hypothesized that there would be a significant relationship. An additional goal was to analyze whether students' self-rated communication skills differ according to their personality traits.…”
Section: Introductionmentioning
confidence: 99%